Managing Eczema with Homeopathy: A Review of Current Approaches (Homoeopathy for All, 2023)
Eczema is a prevalent skin condition  that is long-lasting, not contagious,  and is characterized by dry skin, red  scaly patches in one area, intense  itchiness, and skin discomfort. This  the skin becomes less capable of  retaining moisture and safeguarding  against bacteria, irritants, allergens,  and environmental factors such  as tobacco smoke. Other causes  include the excessive presence of  Staphylococcus aureus bacteria on  the skin.3condition can also be referred to  as atopic eczema, neurodermatitis,  or atopic dermatitis.1 It affects  proportion of 20% children’s and  10% adults’ population in India and  ranks as the 15th most common  non-fatal disease worldwide and  is the leading skin disease in terms  of disability-adjusted life years  (DALYs). The skin eruptions linked with  eczema are recognizable due to the  presence of small raised bumps,  formation of crusts and scales,  fluid-filled blisters on reddened and  swollen skin. Though, in darker  skin, it might be tough to recognize  the redness. When the eruptions or  scales persist for long periods, the  skin might thicken resulting in a  condition called lichenification.2
Keywords: prevalent; allergens; population